2012
DOI: 10.1590/s2176-94512012000600015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of occlusal factors in patients with temporomandibular joint disorder

Abstract: OBJECTIVE: The aim of this study was to determine the prevalence and the relation between the main occlusal factors and the temporomandibular disorder (TMD). METHODS: We analyzed 100 patients (50 diagnosed with TMD and 50 asymptomatic volunteers, control group) through a questionnaire that classified TMD as absent, mild, moderate and severe. Then, an evaluation was made of intraoral occlusal factors: Absence of posterior teeth, wear facets, overjet, overbite, open bite, posterior crossbite, sagittal relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 21 publications
2
21
0
7
Order By: Relevance
“…The criteria for the classification of the malocclusion were based on Angle's classification (1899): subjects who presented one or more of the following conditions were considered as having malocclusion: Angle Class II or III molar relationship, increased overjet (incisors with overjet >4 mm), increased overbite (incisors overbite >4 mm), anterior and/or posterior crossbite, anterior and/or posterior open bite; absence of dental elements …”
Section: Methodsmentioning
confidence: 99%
“…The criteria for the classification of the malocclusion were based on Angle's classification (1899): subjects who presented one or more of the following conditions were considered as having malocclusion: Angle Class II or III molar relationship, increased overjet (incisors with overjet >4 mm), increased overbite (incisors overbite >4 mm), anterior and/or posterior crossbite, anterior and/or posterior open bite; absence of dental elements …”
Section: Methodsmentioning
confidence: 99%
“…The association between tooth loss and temporomandibular disorders (TMD) remains controversial [7,8]. Therefore, the authors are interested to investigate whether the number of missing teeth are associated with temporomandibular disorders in RSGMP FKG USU patients in terms of the number of missing teeth, the number of dental quadrants with missing posterior teeth and the number of occlusal support.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Mr. Sousa et alno relationship was found between side occlusion and TMD problems that are aligned with the results of the present study (4). 14 ABCMED 6(3): [11][12][13][14][15] This study showed that 16.33 percent of Group function side occlusion, 13.23 percent had side occlusion of Anterior Group function and 70.4 percent had side occlusion of canine raise.…”
Section: Discussionmentioning
confidence: 99%
“…ABCMED 6(3): [11][12][13][14][15] abnormal muscle or ligament connection 5) Stress: Stress leads to bruxism or clenching (5)(6)(7).…”
mentioning
confidence: 99%
See 1 more Smart Citation